The value of fasting in the diagnosis of medium-chain acyl-CoA dehydrogenase deficiency - Carmen R Vargas; Marion Deon; Angela Sitta; Daniella M Coelho; Patricia D Silva; Larissa Murussi; Laura V Fleith; Carolina Crespo; Moacir Wajner; Maria Teresa V Sanseverino (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Female patient carrier of medium-chain acyl-CoA dehydrogenase deficiency (MCADD) with recurrent clinical episodes of hypoglycemia and altered level of consciousness, presented changes in blood acylcarnitine profile by tandem mass spectrometry and in the urinary organic acid analysis by gas chromatography/mass spectrometry (GC/MS). This case demonstrates the importance of fasting prior biological sample collection (when possible) when MCADD is suspected, and emphasizes that the time/momentum of biological sample collection is crucial to diagnosis, considering the possibility that MCADD is underdiagnosed in Brazil.